GGE BIPLOT ANALYSIS FOR GENOTYPE X ENVIRONMENT INTERACTION ON YIELD TRAIT OF HIGH FE CONTENT RICE GENOTYPES IN INDONESIAN IRRIGATED ENVIRONMENTS - Untung Susanto; Wage R. Rohaeni; Sarah B. Johnson; Ali Jamil (AGRIVITA, Journal of Agricultural Science, 2015)
The prefalence of Iron (Fe) defficiency in Indonesia is around 31 – 63.5 %.  High Fe content rice lines had been developed to overcome the problem. This study was aimed to explore the effect of genotype (G) and genotype × environment interaction (GEI) on yield of 21 high Fe content rice genotypes under 5 irrigated field environments. The research was conducted at DS 2011 in 2 locations and DS 2012 in 3 locations following randomized complete block design with three replications in each location. Combined analysis of variance showed genotype x environment interaction at 1% probability level, where G and GEI captured totally 88.8% of total variability. There were two Mega-environments constructed, i.e. Mega-E1that contained environments of trials in dry season 2011 (E4 and E5) with the winner of G12 (BP9474C-1-1-B) and Mega-E2 that contained environments of trials in dry season 2012 (E1, E2, and E3) with the winner of G3 (A69-1). E1 (Subang, DS 2012), E2 (Karawang, DS 2012), and E3 (Indramaru, DS 2012) had good discriminativeness and representasiveness for yield trait of high Fe content rice lines. Mean performance and stability of genotypes indicated that G3 (A69-1; average 6.72 t/ha) was highly stable with high yield.